An Exploration of Mathematical Elements in Sasambo Culture as a Resource for Ethnomathematics Based Learning - Yuntawati, Yuntawati; Aziz, Lalu Abdul (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to explore the mathematical elements embedded in Sasambo culture (Sasak, Samawa, and Mbojo) and their potential as learning resources for ethnomathematics-based mathematics education. Using a qualitative approach through literature review, the study analyzed scientific articles obtained from systematic searches on Google Scholar with keywords related to Sasambo ethnomathematics. The findings reveal that Sasambo cultural heritage contains a wide range of mathematical concepts, including plane and solid geometry, patterns, symmetry, geometric transformations, measurement, and problem-solving strategies. These concepts are reflected in traditional architecture such as Bale Tani, Uma Lengge, and Istana Dalam Loka; in the geometric patterns of Sasak and Tembe Nggoli weaving arts; and in cultural activities and traditional games such as Perisean, Barapan Kebo, Nyongkolan, and Dengklaq. The study highlights the potential of integrating these cultural elements into mathematics learning to make it more contextual, meaningful, and engaging for students. Additionally, this integration fosters students' cultural identity and appreciation of local wisdom. The study concludes that systematic efforts are needed to develop culturally-based instructional materials and to provide teacher training on ethnomathematics integration. Such efforts will not only improve students’ mathematical understanding but also strengthen their connection to local cultural heritage, making mathematics learning more relevant to their daily lives.